TANGGUNG JAWAB GANTI KERUGIAN AKIBAT KELALAIAN MASKAPAI PENERBANGAN BERDASARKAN UNDANGUNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI TERHADAP PUTUSAN NO. 433/PDT.G/2019/PN.JKT.PST) - Felix Pranoto; Ariawan ariawan (Jurnal Hukum Adigama, 2021)
Service standard is a benchmark used as a guideline for the implementation of domestic scheduled commercial air transportation services and a reference for assessing service quality which is the obligation of scheduled commercial air transportation business entities to prospective passengers and economy class passengers in the context of quality, fast, and easy services. In the case of David M.L. Tobing, the absence of multimedia facilities that should have become the standard of maximum service standards. What is the responsibility of airlines to passengers due to negligence in supervision that causes the rights of passengers/consumers to be not fulfilled based on Law number 8 of 1999 concerning Consumer Protection? The author uses normative legal research methods using interview data as supporting data. The results of the study reveal that there is a form of responsibility in accordance with what has been regulated in Article 1365 of the Civil Code, namely every act that violates the law, causes harm to others, obliges people because of their mistakes to compensate for the loss. Business actors are responsible for providing compensation for pollution, damage, and/or consumer losses as a result of using traded goods and/or services.